Laminate
The laminate structure with a high-resistance Group 13 nitride single crystal substrate and ε-Ga2O3 semiconductor layer addresses the peeling issue, ensuring stable film formation for larger sizes and enhancing semiconductor device performance.
Patent Information
- Application Number
- JP2023542233
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-20
- Filing Date
- 2022-06-07
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-06-07
AI Technical Summary
ε-Ga2O3 semiconductor layers formed by heteroepitaxial growth on substrates like GaN or AlN tend to peel off easily, especially for larger sizes, leading to increased peeling issues.
A laminate structure is developed with a high-resistance Group 13 nitride single crystal as the underlying substrate, featuring a semiconductor layer composed of ε-Ga2O3 or a solid solution, which includes dopants like Zn, Fe, or Mn, and has a specific resistance of 1.00×10^2 Ω cm or more and a thickness of 200 μm or more, reducing peeling.
The laminate structure effectively prevents the semiconductor layer from peeling off the substrate, allowing for larger film sizes and improved stability, facilitating the production of high-quality semiconductor devices.
Smart Images

Figure 0007612029000002 
Figure 0007612029000003 
Figure 0007612029000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, and more particularly to a laminate having an ε-Ga2O3-based semiconductor layer and a Group 13 nitride single crystal. [Background technology]
[0002] In recent years, gallium oxide (Ga2O3) has been attracting attention as a semiconductor material. Gallium oxide is known to have five crystal structures: α, β, γ, δ, and ε. Of these, ε-Ga2O3 has a band gap of approximately 5 eV and is highly stable up to approximately 870°C, so it has attracted a great deal of attention as a next-generation power semiconductor material with high voltage resistance and low power consumption.
[0003] However, since ε-Ga2O3 is a metastable phase, single crystal substrates have not been put to practical use, and it is generally formed by heteroepitaxial growth using HVPE (halide vapor phase epitaxy) or mist CVD (chemical vapor phase epitaxy). For example, Patent Document 1 (Patent No. 6436538) discloses ε-Ga2O3 single crystals with low impurity concentration that are applicable to semiconductor elements, which are produced using the HVPE method. Non-Patent Document 1 (Yuichi Oshima et al. "Epitaxial growth of phase-pure ε-Ga2O3by halide vapor phase epitaxy" J. Appl. Phys, 118, 085301 (2015)) discloses that ε-Ga2O3 was epitaxially grown by the HVPE method.
[0004] Meanwhile, high electron mobility transistors (HEMTs) are being actively developed as high-frequency devices such as power amplifiers for mobile phone base stations. For example, Patent Document 2 (Patent No. 6018360) discloses a compound semiconductor device (GaN-based HEMT) that can obtain an electron transport layer and an electron supply layer with good crystallinity. In addition, in order to further increase the withstand voltage of HEMTs, the application of ε-Ga2O3-based materials having a band gap exceeding that of GaN-based materials has attracted attention. For example, Patent Document 3 (JP Patent Publication No. 2019-46984) discloses a method for manufacturing a semiconductor device with excellent semiconductor characteristics using ε-Ga2O3. It is described that this semiconductor device is manufactured by forming, by a mist CVD method, a first semiconductor film containing a semiconductor crystal having a metastable crystal structure as a main component, and a second semiconductor film (mainly ε-Ga2O3) having a composition different from the main component of the first semiconductor film and containing a semiconductor crystal having a hexagonal crystal structure as a main component.
[0005] As mentioned above, only a method of forming ε-Ga2O3 by heteroepitaxial growth is known, and it is necessary to form a film on a heterogeneous substrate such as GaN. The GaN template used for such film formation is a GaN film formed on a sapphire substrate or a SiC substrate. For example, Non-Patent Document 2 (Stefano Leone et al. "Epitaxial growth of GaN / Ga2O3and Ga2O3 / GaN heterostructures for novel high electron mobility transistors" Journal of Crystal Growth 534 (2020) 125511) describes a method of forming an ε-Ga2O3 layer on a GaN template. In addition, Patent Document 1 describes a method of forming an ε-Ga2O3 film on a GaN single crystal. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6436538
Patent Document 2
Patent Document 3
Non-Patent Document
[0007]
Non-Patent Document 1
Non-Patent Document 2
Non-Patent Document 3
Non-Patent Document 4
Summary of the Invention
[0008] However, an ε-Ga2O3 film formed by heteroepitaxial growth on a GaN template or a GaN single crystal is prone to peeling off from the base substrate, and there is a problem that the number of peeled off portions increases when the ε-Ga2O3 film is formed on a size of 2 inches or more. Peeling is also likely to occur not only when a GaN template or a GaN single crystal is used, but also when an AlN template or the like is used. For example, Patent Document 1 describes a method of forming an ε-Ga2O3 layer on an AlN template, but there is a problem that the number of peeled off portions increases when the ε-Ga2O3 film is formed on a size of 2 inches or more.
[0009] The present inventors have now discovered that by forming an ε-Ga2O3-based semiconductor layer on a high-resistivity, thick group 13 nitride single crystal as a base substrate, it is possible to provide a laminate in which the ε-Ga2O3-based semiconductor layer is unlikely to peel off from the base substrate.
[0010] Therefore, an object of the present invention is to provide a laminate in which an ε-Ga2O3-based semiconductor layer is unlikely to peel off from a base substrate.
[0011] According to the present invention, the following aspects are provided. [Aspect 1] a semiconductor layer composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution; Resistivity at 25°C is 1.00×10 2 A high resistivity group 13 nitride single crystal having a resistivity of Ω·cm or more and a thickness of 200 μm or more; A laminate having a two-layer structure composed of: [Aspect 2] 2. The laminate according to aspect 1, wherein the high-resistance Group 13 nitride single crystal is any one single crystal selected from GaN, AlN, and BN. [Aspect 3] The high-resistance group 13 nitride single crystal is a GaN single crystal, and Zn is added as a dopant at a concentration of 1.00×10 18 ~2.00×10 19 atoms / cm 3 The laminate of embodiment 2, comprising: [Aspect 4] The high-resistance group 13 nitride single crystal is a GaN single crystal, and contains Fe as a dopant at a concentration of 1.00×10 18 ~2.00×10 19 atoms / cm 3 The laminate according to any one of the preceding claims, wherein the laminate comprises [Aspect 5] The high-resistance group 13 nitride single crystal is a GaN single crystal, and Mn is added as a dopant at a concentration of 1.00×10 18 ~2.00×10 19 atoms / cm 3 The laminate according to any one of aspects 2 to 4, wherein the concentration of [Aspect 6] The Zn concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of aspects 1 to 5, wherein: [Aspect 7] The Fe concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of aspects 1 to 6, wherein: [Aspect 8] The Mn concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of aspects 1 to 7, wherein: [Aspect 9] The ratio t1 / t2 of the thickness t1 of the semiconductor layer to the thickness t2 of the high-resistance Group 13 nitride single crystal is 1.00×10 -5 The laminate according to any one of aspects 1 to 8, wherein the average molecular weight is 1.00 or less. [Brief description of the drawings]
[0012] [Figure 1] 1 is a horizontal cross-sectional view of an upper portion of the crystal substrate production apparatus 10. FIG. [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] 2 is a cross-sectional view of the pressure-resistant vessel 12 for explaining the overall configuration of the pressure-resistant vessel 12. FIG. [Figure 4]4 is a cross-sectional view of the pressure vessel 12 when the pressure vessel 12 is tilted by a rocking device 70. FIG. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing the configuration of a vapor phase growth apparatus using the HVPE method. [Figure 6] FIG. 1 is a schematic cross-sectional view showing the configuration of a mist CVD apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Laminate The laminate of the present invention has a two-layer structure composed of a semiconductor layer composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution and a high-resistance group 13 nitride single crystal. The high-resistance group 13 nitride single crystal has a specific resistance of 1.00×10 at 25° C. 2 The ε-Ga2O3-based semiconductor layer has a resistivity of Ω·cm or more and a thickness of 200 μm or more. In this way, by forming an ε-Ga2O3-based semiconductor layer on a thick group 13 nitride single crystal with high resistance as a base substrate, a laminate can be provided in which the ε-Ga2O3-based semiconductor layer is not easily peeled off from the base substrate. As mentioned above, there was a problem that an ε-Ga2O3 film formed on a heterogeneous substrate such as GaN by heteroepitaxial growth is easily peeled off from the base substrate, but the laminate of the present invention can conveniently solve this problem.
[0014] Although the reason why the use of a high-resistance, thick group 13 nitride single crystal as the base substrate on which the ε-Ga2O3-based semiconductor layer is formed is able to suppress the peeling of the ε-Ga2O3-based semiconductor layer as in the present invention is unclear, it can be assumed, for example, as follows. It is known that when an ε-Ga2O3-based semiconductor layer is formed on a group 13 nitride, a two-dimensional electron gas layer is formed due to spontaneous polarization and the piezoelectric effect. It can be assumed that the use of a high-resistance, thick group 13 nitride single crystal as the base substrate causes a change in the two-dimensional electron gas layer that is generated when the ε-Ga2O3-based semiconductor layer is stacked, making it difficult to peel off due to some kind of electrical effect.
[0015] In the laminate of the present invention, the ratio t1 / t2 of the thickness t1 of the semiconductor layer to the thickness t2 of the high-resistance Group 13 nitride single crystal is preferably small, and is preferably 1.00 or less, and more preferably 0.1 or less. There is no particular lower limit to this t1 / t2, but it is preferably 1.00×10 -5 It is preferable that t1 / t2 is 1.00×10 -5 It is preferably 1.00 to 1.00, and more preferably 1.00 × 10 -5 ~1.00×10 -1 This improves the effect of suppressing peeling of the semiconductor layer.
[0016] The diameter of the laminate is preferably larger because a larger number of chips can be produced, and is preferably 50.8 mm or more, more preferably 100 mm or more, and further preferably 150 mm or more. There is no particular upper limit to this size, but it is preferably 200 mm or less.
[0017] Highly resistive group 13 nitride single crystal The high-resistance group 13 nitride single crystal in the laminate of the present invention has a specific resistance of 1.00×10 at 25° C. 2 Ω·cm or more and a thickness of 200 μm or more. GaN templates and GaN single crystals that have been used conventionally as base substrates have low resistance. Even if a GaN film or GaN single crystal does not contain an n-type dopant (non-doped), the resistance is low due to the absence of N and the presence of O as an impurity. For example, it is unclear whether the GaN single crystal of Patent Document 1 and the GaN template of Non-Patent Document 2 are n-type doped, but it is believed that the resistance would be low even if they were non-doped. On the other hand, the group 13 nitride single crystal of the laminate of the present invention has a specific resistance of 1.00×10 at 25° C. 2 The resistivity of the high-resistance group 13 nitride single crystal at 25°C is preferably high, and is preferably 1.00×10 4 Ω cm or more, preferably 1.00×10 5 Ω cm or more, more preferably 1.00×108 Ω cm or more, particularly preferably 1.00×10 11 The resistivity is 1.00×10 18 Ω·cm or less is preferable.
[0018] The thickness of the high-resistance group 13 nitride single crystal is preferably thicker from the viewpoint of suppressing peeling of the ε-Ga2O3-based semiconductor layer, and is preferably 300 μm or more, more preferably 500 μm or more, with no particular upper limit. On the other hand, the thickness is preferably thinner from the viewpoint of cost and heat dissipation, and is preferably 1000 μm or less, more preferably 500 μm or less. In order to achieve both the viewpoint of suppressing peeling and the viewpoint of cost and heat dissipation, the thickness of the high-resistance group 13 nitride single crystal is preferably 300 to 1000 μm.
[0019] The high-resistance group 13 nitride single crystal is preferably any one type of single crystal selected from GaN, AlN, and BN, and more preferably GaN or AlN. From the viewpoints of single crystal size and cost, GaN is preferable. On the other hand, AlN is preferable from the viewpoint of insulation.
[0020] When the high-resistance Group 13 nitride single crystal is a GaN single crystal, it preferably contains a dopant. Examples of the dopant include Be, Mg, Zn, Fe, Mn, and Cd, and preferably Zn, Fe, or Mn. The dopant is added to the high-resistance Group 13 nitride single crystal in an amount of 1.00×10 18 ~2.00×10 19 atoms / cm 3 That is, the high-resistance group 13 nitride single crystal is a GaN single crystal, and preferably contains Zn, Fe, or Mn as a dopant at a concentration of 1.00×10 18 ~2.00×10 19 atoms / cm 3 It is preferable that the dopant concentration is 1.00×10 18 atoms / cm 3 By setting the dopant concentration at 2.00×10 or more, it is possible to prevent the resistance from dropping too much. 19 atoms / cm3 or less, the quality of the GaN single crystal can be maintained. Here, as described above, the GaN templates and GaN single crystals that have been conventionally used as base substrates have low resistance even in a non-doped state. On the other hand, in the present invention, a high-resistance Group 13 nitride single crystal can be efficiently obtained by counter-doping the Group 13 nitride single crystal with Zn or the like.
[0021] Semiconductor Layer The semiconductor layer (hereinafter, sometimes referred to as a semiconductor film) constituting the laminate of the present invention is composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution. Therefore, this semiconductor layer can be referred to as an ε-Ga2O3-based semiconductor layer. An ε-Ga2O3-based solid solution is one in which other components are dissolved in ε-Ga2O3. For example, the ε-Ga2O3-based semiconductor layer can be composed of an ε-Ga2O3-based solid solution in which one or more components selected from the group consisting of Cr2O3, Fe2O3, Ti2O3, V2O3, Ir2O3, Rh2O3, In2O3, and Al2O3 are dissolved in ε-Ga2O3. In addition, by dissolving these components in solid solution, it becomes possible to control the band gap, electrical properties, and / or lattice constant of the semiconductor film. The amount of these components dissolved in solid solution can be appropriately changed according to the desired properties.
[0022] However, the crystal structure of ε-Ga2O3 has not been fully elucidated at the current technical level, and it is possible that what is identified as κ-Ga2O3 in crystal structure analysis may also be identified as ε-Ga2O3, or what is identified as ε-Ga2O3 may also be identified as κ-Ga2O3. For example, Non-Patent Document 3 (Ildiko Cora et al. "The real structure of ε-Ga2O3 and its relation to κ-phase," CrystEngComm, 2017, 19, 1509-1516) suggests that the crystal structure of ε-Ga2O3 (hexagonal crystal) and the crystal structure of κ-Ga2O3 (rectangular crystal) may be confused depending on the resolution of the probe technology. Therefore, in this specification, the term "ε-Ga2O3" refers not only to ε-Ga2O3 but also to κ-Ga2O3. That is, in this specification, even if it is identified as having the crystal structure of κ-Ga2O3, it is considered to be "ε-Ga2O3" and is included in the term "ε-Ga2O3".
[0023] From the viewpoint of stably controlling the semiconductor characteristics of the ε-Ga2O3-based semiconductor layer, it is preferable that Zn, Fe, or Mn is not diffused from the high-resistance group 13 nitride single crystal doped with Zn, Fe, or Mn into the ε-Ga2O3-based semiconductor layer. In other words, it is preferable that the concentration of Zn, Fe, or Mn in the ε-Ga2O3-based semiconductor layer is low. From this viewpoint, the concentration of Zn, Fe, or Mn in the ε-Ga2O3-based semiconductor layer is preferably 1.00×10 16 atoms / cm 3 Of course, Zn, Fe, or Mn may be contained in the semiconductor layer because they can act as p-type dopants for Ga2O3, but even in this case, it becomes easier to control the semiconductor characteristics by preventing the Zn, Fe, or Mn derived from the high-resistance group 13 nitride single crystal from diffusing into the semiconductor layer.
[0024] The orientation direction of the ε-Ga2O3-based semiconductor layer of the present invention in the approximately normal direction is not particularly limited, but is preferably c-axis orientation. However, a typical ε-Ga2O3-based semiconductor layer is composed of ε-Ga2O3 or a mixed crystal of ε-Ga2O3 and a different material, and is oriented in two axes, the c-axis and the a-axis. As long as it is oriented in two axes, the ε-Ga2O3-based semiconductor layer may be a mosaic crystal. A mosaic crystal is a collection of crystals that do not have clear grain boundaries, but whose orientation orientations are slightly different in one or both of the c-axis and the a-axis. The method for evaluating the biaxial orientation is not particularly limited, but known analytical methods such as EBSD (Electron Back Scatter Diffraction Patterns) method and X-ray pole figures can be used. For example, when the EBSD method is used, the surface (film surface) of the biaxially oriented ε-Ga2O3 layer or the inverse pole figure mapping of a cross section perpendicular to the surface is measured. In the obtained inverse pole figure mapping, when two conditions are satisfied, namely (A) the film surface is oriented in a specific direction, and (B) the film surface is oriented in an axis perpendicular to the orientation direction of the approximately normal direction in a direction perpendicular to the normal direction, the film surface can be defined as being oriented in two axes, the approximately normal direction and the approximately film surface direction. In other words, when the above two conditions are satisfied, it is determined that the film surface is oriented in two axes, the c-axis and the a-axis. For example, when the approximately normal direction of the film surface is oriented in the c-axis, it is sufficient that the approximately film surface direction is oriented in a specific direction (e.g., the a-axis) perpendicular to the c-axis.
[0025] The semiconductor layer contains 1.0×10 Group 14 elements as dopants. 15 ~1.0×10 21 / cm 3 Here, the group 14 element refers to the group 14 element according to the periodic table established by IUPAC (International Union of Pure and Applied Chemistry), specifically, any one of carbon (C), silicon (Si), germanium (Ge), tin (Sn) and lead (Pb). The amount of dopant can be appropriately changed according to the desired characteristics, but is preferably 1.0×10 15 ~1.0×10 21 / cm 3 , more preferably 1.0×10 17~1.0×10 19 / cm 3 It is preferable that these dopants are uniformly distributed in the layer, and that the concentrations on one surface (front surface) and the opposite surface (back surface) are approximately the same. In other words, it is preferable that the semiconductor layer uniformly contains Group 14 elements as dopants in the above ratios.
[0026] The thickness of the semiconductor layer may be adjusted appropriately from the viewpoint of cost and required characteristics. That is, if the thickness is too thick, it takes a long time to form the film, so it is preferable that the thickness is not excessively thick from the viewpoint of cost. However, it is preferable to make the layer moderately thick according to the necessity of the target semiconductor characteristics. In this way, the thickness of the layer may be adjusted appropriately according to the desired characteristics, and is preferably 0.01 to 400 μm, more preferably 0.1 to 50 μm. By setting the thickness in such a range, it is possible to achieve both cost and semiconductor characteristics.
[0027] The laminate is preferably 20 cm 2 More than 70cm, preferably 70cm 2 More than 170cm, more preferably 2 By increasing the area of the laminate in this way, it becomes possible to obtain a large number of semiconductor elements from one laminate, and manufacturing costs can be reduced. There is no particular upper limit to the size of the laminate, but typically, it is 700 cm2 on one side. 2 The following is the result.
[0028] Manufacturing method for high-resistance group 13 nitride single crystals A preferred method for producing a high-resistance group 13 nitride single crystal will be described below with reference to the drawings. Fig. 1 is a horizontal cross-sectional view of the upper part of a crystal plate production apparatus 10, Fig. 2 is a cross-sectional view taken along the line AA in Fig. 1, Fig. 3 is a cross-sectional view of the pressure vessel 12 for explaining the overall configuration of the pressure vessel 12, and Fig. 4 is a cross-sectional view of the pressure vessel 12 when tilted by a rocking device 70. For convenience, peripheral equipment such as a nitrogen gas cylinder 22 and a vacuum pump 26 are omitted from Figs. 1 and 2.
[0029] As shown in FIG. 1, a crystal substrate production apparatus 10 includes a pressure-resistant vessel 12 and a rocking device 70 capable of rocking the pressure-resistant vessel 12 .
[0030] As shown in FIG. 3, the pressure vessel 12 includes a vessel body 12a with a brim and a vessel lid 12b with a brim. The pressure vessel 12 has a heating space 16 surrounded by a heater cover 14. The heating space 16 has an internal temperature that can be adjusted by an upper heater 18a, a middle heater 18b, and a lower heater 18c that are arranged vertically on the side of the heater cover 14, as well as a bottom heater 18d that is arranged on the bottom surface of the heater cover 14. The heating space 16 has high thermal insulation properties due to a heater insulation material 20 that covers the periphery of the heater cover 14. The pressure vessel 12 is connected to nitrogen introduction pipes 24a and 24b of a nitrogen gas cylinder 22 and a vacuum suction pipe 28 of a vacuum pump 26. The nitrogen introduction pipe 24a is capable of introducing nitrogen gas into the container 42 by penetrating the pressure vessel 12, the heater insulation material 20, the heater cover 14, and the container 42. The nitrogen introduction pipe 24b penetrates the pressure vessel 12 and can introduce nitrogen gas into the pressure vessel 12. The nitrogen introduction pipes 24a and 24b are made of flexible pipes from the nitrogen gas cylinder 22 to the pressure vessel 12. The nitrogen introduction pipes 24a and 24b are equipped with a mass flow controller 25 capable of adjusting the flow rate, and the nitrogen introduction pipe 24b is equipped with a valve 27 capable of opening and closing the pipe. The vacuum piping 28 penetrates the pressure vessel 12 and opens into the gap between the pressure vessel 12 and the heater insulation material 20. The heater cover 14 is not completely sealed, so if the outside of the heater cover 14 is in a vacuum state, the inside is also in a vacuum state. This vacuum piping 28 is made of flexible pipes. The pressure vessel 12 is further equipped with a nitrogen exhaust pipe 48 with a valve 49. This nitrogen exhaust pipe 48 is designed to communicate the inside of the container 42 with the outside air by opening the valve 49. The portion of the nitrogen exhaust pipe 48 that is located outside the pressure vessel 12 is made of a flexible pipe.
[0031] Inside the pressure vessel 12, a container 42 is placed on the lifting stand 30. The container 42 includes a bottomed, cylindrical container body 42a made of Inconel and a container lid 42b made of Inconel that closes the upper opening of the container body 42a. The container lid 42b is provided with a nitrogen inlet pipe 24a and a nitrogen exhaust pipe 48 for exhausting the introduced nitrogen that overflows from the internal space of the container 42. Inside the container 42, an intermediate vessel 60 having a bottomed, cylindrical body and a lid is accommodated, and inside the intermediate vessel 60, an alumina growth vessel 50 having a bottomed, cylindrical body and a lid is placed. The growth vessel 50 contains a mixed melt of growth raw materials (e.g., sodium / gallium / zinc / carbon), and a disk-shaped alumina seed crystal substrate tray 52 is placed in the mixed melt. One end of the seed crystal substrate tray 52 contacts a tray stand 56, and the other end contacts the bottom surface of the growth vessel 50. The seed crystal substrate tray 52 has a recess in the center for fitting a disk-shaped seed crystal substrate 54. The seed crystal substrate 54 may be a sapphire substrate having a thin film of GaN formed on the surface thereof by a vapor phase method, or a GaN substrate.
[0032] As shown in FIG. 1 and FIG. 2, the rocking device 70 includes a base 72 on which the pressure vessel 12 is placed, brackets 74 attached to the upper parts of four pillars 73 erected around the base 72, and a telescopic mechanism 76 connected between each bracket 74 and the base 72. The base 72 is a plate-like member having a substantially rectangular shape in a plan view, and the pressure vessel 12 can be placed in the center. The bracket 74 supports an actuator 78 having a servo motor so that it can be rocked by a horizontal shaft. The telescopic mechanism 76 includes an actuator 78 having a cylinder 77 attached to its lower part, a movable shaft 80 attached to the cylinder 77 and capable of extending and retracting in the vertical direction via a ball screw, a universal joint 82 attached to the lower end of the movable shaft 80, and a support shaft 84 fixed to the base 72 and supporting the universal joint 82. In FIG. 2, in a pair of telescopic mechanisms 76 facing each other, one movable shaft 80 (the right movable shaft 80) of the left and right telescopic mechanisms 76 is extended and the other movable shaft 80 (the left movable shaft 80) is contracted, so that the base 72 is inclined obliquely as shown in FIG. 4. At this time, each support shaft 84 is fixed to the base 72, but a universal joint 82 corresponding to angles in all directions is interposed between the support shaft 84 and the movable shaft 80, and the actuator 78 is attached to the bracket 74 so as to be swingable, so that the base 72 can be inclined obliquely without any trouble. If the four actuators 78 are controlled by a sequencer (not shown), the base 72 can be rotated in a state inclined by a predetermined angle with respect to the horizontal plane. This makes it possible to rotate the mixed melt in the growth vessel 50 in the pressure-resistant vessel 12 placed on the base 72, and to cause vertical convection in the mixed melt.
[0033] A preferred use example of the crystal substrate manufacturing apparatus 10 thus configured will be described. The crystal substrate manufacturing apparatus 10 is used to manufacture high-resistance group 13 nitride single crystals by, for example, the flux method. The following describes an example of manufacturing a high-resistance group 13 nitride single crystal doped with Zn (hereinafter, sometimes referred to as a Zn-doped GaN single crystal). In this case, a GaN template is prepared as the seed crystal substrate 54, metallic gallium is prepared as the group 13 metal, and metallic sodium is prepared as the flux. First, as shown in FIG. 3, the seed crystal substrate 54 is immersed in a mixed melt containing metallic gallium, metallic sodium, metallic zinc, and carbon in the growth vessel 50. Next, the inside of the pressure-resistant vessel 12 is filled with 1×10 -2 The chamber is evacuated to the Pa range to reduce the moisture and oxygen remaining inside. Nitrogen gas is then introduced to a predetermined pressure, and the heaters 18a to 18d are controlled so that the heating space 16 reaches a predetermined crystal growth temperature while the nitrogen gas is continuously supplied to the mixed melt. The actuator 78 is then controlled to rotate the base at a predetermined speed (for example, 1 to 10 rpm) while switching between clockwise and counterclockwise at a predetermined period (for example, 30 to 300 seconds) while tilting the base at a predetermined angle (for example, 5 to 15°) with respect to the horizontal plane, forcibly stirring the contents of the growth vessel 50. This allows the mixed melt to be constantly moved relative to the seed crystal substrate 54. At this time, it is preferable to have the surface of the seed crystal substrate 54 with the fastest crystal growth facing upward. This allows the seed crystal to be constantly supplied with raw material containing dissolved nitrogen at the gas-liquid interface, making it easier to obtain a high-quality group 13 metal nitride. By maintaining this state, a single crystal of Zn-doped GaN grows on the seed crystal substrate 54 in the mixed melt. In addition, adding an appropriate amount of carbon to the mixed melt suppresses the inhibition of nitridation of the gallium raw material by zinc. After cooling, the Zn-doped GaN single crystal grown in the mixed melt in the growth vessel 50 can be recovered by adding an organic solvent (e.g., a lower alcohol such as isopropanol or ethanol) to the vessel and dissolving unnecessary substances such as flux in the organic solvent.
[0034] As described above, when manufacturing Zn-doped GaN single crystals, the crystal growth temperature is preferably set to 800 to 950°C, more preferably 850 to 900°C. To make the temperature of the heating space 16 uniform, it is preferable to set the temperatures of the upper heater 18a, the middle heater 18b, the lower heater 18c, and the bottom heater 18d in that order so that the temperatures increase, or to set the upper heater 18a and the middle heater 18b to the same temperature T1 and the lower heater 18c and the bottom heater 18d to a temperature T2 higher than the temperature T1. The pressure of the nitrogen gas is preferably set to 2 to 5 MPa, more preferably 2.5 to 4 MPa. To adjust the pressure of the nitrogen gas, first, the vacuum pump 26 is driven to set the internal pressure of the pressure-resistant vessel 12 to a high vacuum state (for example, 1 Pa or less or 0.1 Pa or less) through the vacuum piping 28, and then the vacuum piping 28 is closed by a valve (not shown), and nitrogen gas is supplied from the nitrogen gas cylinder 22 to the heating space 16 through the nitrogen introduction pipe 24a. During the growth of the GaN crystal, in order to prevent the atmosphere inside the container 42 from being contaminated by impurities diffusing from the structures inside the furnace, nitrogen gas is continuously supplied to the heating space 16 during the crystal growth at a predetermined flow rate by the mass flow controller 25. During this time, the nitrogen introduction pipe 24b is closed by the valve 27. Note that the overflowing nitrogen gas is released to the atmosphere through the nitrogen exhaust pipe 48.
[0035] As described above in detail, the crystal substrate manufacturing apparatus 10 can preferably produce a thick Zn-doped GaN single crystal having a high resistivity. In addition, since the contents in the growth vessel 50 are forcibly stirred, Zn is easily dispersed uniformly, and the Zn-doped GaN single crystal is easily homogenous. Furthermore, since the bottom heater 18d is arranged in addition to the upper, middle, and lower heaters 18a to 18c, the entire heating space 16 can be kept at a uniform temperature, including the vicinity of the bottom surface where the temperature is likely to be non-uniform. Fe-doped GaN single crystals or Mn-doped GaN single crystals can also be produced by the same method as the Zn-doped GaN single crystal.
[0036] It goes without saying that the method for producing high-resistance group 13 nitride single crystal is not limited to the above-mentioned production form, and can be carried out in various forms as long as it falls within the technical scope of the present invention.
[0037] For example, in the above-described manufacturing form, the oscillating device 70 is used to rotate and circulate the melt in the growth vessel 50 in the pressure-resistant vessel 12 placed on the base 72, but a rotation mechanism that rotates the base 72 may be used to rotate and circulate the melt instead of the oscillating device 70. Furthermore, when producing an AlN single crystal as the high-resistance group 13 nitride single crystal, the AlN single crystal can be produced by existing techniques such as sublimation and HVPE.
[0038] Method for manufacturing semiconductor layer The semiconductor layer can be manufactured by using a high-resistance group 13 nitride single crystal as a base substrate and forming a film of an ε-Ga2O3-based material thereon. There is no particular limitation on the manufacturing method of the ε-Ga2O3-based semiconductor layer, but gas phase methods such as mist CVD, HVPE, MOCVD, and sputtering, and liquid phase methods such as hydrothermal and flux methods are preferred, with mist CVD, HVPE, and hydrothermal being particularly preferred. Of these methods, the HVPE and mist CVD methods are described below.
[0039] The HVPE method (Halide Vapor Phase Epitaxy) is a type of CVD that can be used to form compound semiconductor films such as Ga2O3 and GaN. In this method, gallium halide gas is generated by reacting the Ga raw material with a halide, and is then supplied onto the substrate for film formation. At the same time, O2 gas is supplied onto the substrate for film formation, and the gallium halide gas reacts with the O2 gas to grow Ga2O3 on the substrate for film formation. This method allows for high-speed and thick film growth and has a wide track record in industry, with examples of film formation of not only α-Ga2O3 but also β-Ga2O3 being reported.
[0040] An example of a vapor phase growth apparatus using the HVPE method is shown in Fig. 5. The vapor phase growth apparatus 90 using the HVPE method includes a reactor 100, a susceptor 108 on which a base substrate 106 for film formation is placed, an oxygen source supply source 101, a carrier gas supply source 102, a Ga source supply source 103, a heater 104, and a gas exhaust unit 107. The reactor 100 may be any reactor that does not react with the source material, such as a quartz tube. The heater 104 may be any heater that can heat up to at least 700°C (preferably 900°C or higher), such as a resistance heating heater.
[0041] The Ga source 103 has metal Ga 105 placed therein, and is supplied with halogen gas or hydrogen halide gas, such as HCl. The halogen gas or halogen gas is preferably Cl2 or HCl. The supplied halogen gas or halogen gas reacts with the metal Ga 105 to generate gallium halide gas, which is supplied to the substrate for deposition. The gallium halide gas preferably contains GaCl and / or GaCl3. The oxygen source 101 can supply an oxygen source selected from the group consisting of O2, H2O, and N2O, with O2 being preferred. These oxygen source gases are supplied to the substrate for deposition simultaneously with the gallium halide gas. The Ga source and oxygen source gas may be supplied together with a carrier gas such as N2 or a rare gas.
[0042] The gas exhaust unit 107 may be connected to a vacuum pump such as a diffusion pump or a rotary pump, and may not only exhaust unreacted gas in the reaction furnace 100 but also control the inside of the reaction furnace 100 to a reduced pressure. This can suppress gas phase reactions and improve the growth rate distribution.
[0043] The heater 104 is used to heat the base substrate 106 for film formation to a predetermined temperature, and gallium halide gas and oxygen source gas are simultaneously supplied, thereby forming ε-Ga2O3 on the base substrate 106 for film formation. The film formation temperature is not particularly limited as long as ε-Ga2O3 is formed, but is typically 250°C to 900°C. The partial pressures of the Ga source gas and oxygen source gas are also not particularly limited. For example, the partial pressure of the Ga source gas (gallium halide gas) may be in the range of 0.05 kPa to 10 kPa, and the partial pressure of the oxygen source gas may be in the range of 0.25 kPa to 50 kPa.
[0044] When forming an ε-Ga2O3-based semiconductor layer containing a group 14 element as a dopant, or when forming a mixed crystal film with ε-Ga2O3 containing oxides of In or Al, a separate supply source may be provided to supply the halides, or a mixture of halides may be supplied from the Ga raw material supply source 103. Alternatively, a material containing a group 14 element, In, Al, or the like may be placed in the same location as the metal Ga 105, reacted with halogen gas or hydrogen halide gas, and supplied as a halide. The halide gas supplied to the base substrate 106 reacts with the oxygen raw material gas to become an oxide, similar to gallium halide, and is incorporated into the ε-Ga2O3-based semiconductor film.
[0045] When forming a semiconductor layer by the HVPE method, a single-layer structure can be formed by appropriately controlling the film formation conditions while keeping the supply amounts of Ga source material, oxygen source material, etc. constant. In this way, the semiconductor layer can be formed on the base substrate.
[0046] The mist CVD method is a technique in which a raw material solution is atomized or turned into droplets to generate mist or droplets, which are then transported to a film-forming chamber equipped with a substrate using a carrier gas, where the mist or droplets are thermally decomposed and chemically reacted to form and grow a film on the substrate, and does not require a vacuum process, making it possible to produce a large number of samples in a short period of time. Figure 6 shows an example of a mist CVD device. 6 includes a susceptor 120 on which a substrate 119 is placed, a dilution gas source 112a, a carrier gas source 112b, a flow rate control valve 113a for controlling the flow rate of the dilution gas sent from the dilution gas source 112a, a flow rate control valve 113b for controlling the flow rate of the carrier gas sent from the carrier gas source 112b, a mist generating source 114 in which a raw material solution 114a is stored, a container 115 in which water 115a is stored, an ultrasonic vibrator 116 attached to the bottom surface of the container 115, a quartz tube 117 serving as a film forming chamber, a heater 118 installed around the quartz tube 117, and an exhaust port 121. The susceptor 120 is made of quartz, and the surface on which the substrate 119 is placed is inclined from the horizontal plane.
[0047] The raw material solution 114a used in the mist CVD method is not limited as long as it is a solution that can obtain an ε-Ga2O3-based semiconductor layer, but examples thereof include an organometallic complex or halide of Ga and / or a metal that forms a solid solution with Ga dissolved in a solvent. An example of the organometallic complex is an acetylacetonate complex. In addition, when a dopant is added to the semiconductor layer, a solution of a dopant component may be added to the raw material solution. Furthermore, an additive such as hydrochloric acid may be added to the raw material solution. Water, alcohol, etc. can be used as the solvent.
[0048] Next, the obtained raw solution 114a is atomized or turned into droplets to generate mist or droplets 114b. A preferred example of a method for atomizing or turning into droplets is a method of vibrating the raw solution 114a using an ultrasonic vibrator 116. The obtained mist or droplets 114b are then transported to a film formation chamber using a carrier gas. The carrier gas is not particularly limited, but one or more of inert gases such as oxygen, ozone, and nitrogen, and reducing gases such as hydrogen can be used.
[0049] The film-forming chamber (quartz tube 117) is equipped with a substrate 119. The mist or droplets 114b transported to the film-forming chamber are thermally decomposed and chemically reacted therein to form a film on the substrate 119. The reaction temperature varies depending on the type of raw material solution, but is preferably 300 to 800°C, more preferably 400 to 700°C. The atmosphere in the film-forming chamber is not particularly limited as long as a desired semiconductor film can be obtained, and may be an oxygen gas atmosphere, an inert gas atmosphere, a vacuum or a reducing atmosphere, but an air atmosphere is preferable. In this way, a semiconductor layer can be formed on a base substrate.
[0050] By providing a device structure such as an electron transport layer on the semiconductor layer made of ε-Ga2O3 or ε-Ga2O3-based solid solution obtained as described above, a lateral element such as a HEMT can be formed. In addition, the semiconductor layer itself can be used as the electron transport layer. EXAMPLES
[0051] The present invention will now be further illustrated by the following examples.
[0052] Example 1 (1) Preparation of high-resistivity group 13 nitride (GaN) single crystal substrate First, a 70 nm GaN low-temperature buffer layer was formed at 550°C on the surface of a c-plane sapphire substrate with a diameter of 50.8 mm (2 inches) and a thickness of 0.43 mm. Then, a 10 μm thick GaN thin film was formed by vapor phase deposition at 1050°C to obtain a GaN template that can be used as a seed crystal substrate 54.
[0053] Next, a GaN single crystal doped with Zn was formed on the GaN template by a flux method. Hereinafter, a method for forming a GaN single crystal will be specifically described with reference to FIGS. 1 to 4. First, in a glove box with an argon atmosphere, a tray stand 56 was placed in an alumina crucible serving as a growth vessel 50 having an inner diameter of 70 mm, and a seed crystal substrate tray 52 was placed on the tray stand 56 at an angle of 10° at the center of the bottom surface of the growth vessel 50. The above-mentioned GaN template was placed as a seed crystal substrate 54 at the center of the seed crystal substrate tray 52. Then, 34 g of metallic sodium (Na), 38 g of metallic gallium (Ga), 90 mg of carbon (C), and 175 mg of zinc (Zn) were filled into the growth vessel 50. At this time, the ratio of Ga to Na was 27 mol%, the ratio of Zn to Na was 0.18 mol%, the ratio of Zn to Ga was 0.49 mol%, and the ratio of C to Na was 0.5 mol%. The Zn raw material was a wire-like material with a diameter of 1 mm cut to a length of about 3 mm, and an appropriate amount of the raw material was used. The growth vessel 50 was placed in the intermediate vessel 60, which was then placed in the container body 42a and the container lid 42b was closed, and the container 42 was then placed in the vessel body 12a of the pressure vessel 12, the vessel lid 12b was closed, and the vessel was placed on the base 72. Next, the internal pressure of the pressure vessel 12 was set to a high vacuum state, and then the valve (not shown) of the vacuum piping 28 was closed. Next, nitrogen gas was supplied from the nitrogen gas cylinder 22 into the pressure vessel 12 and the container 42 through the nitrogen introduction pipes 24a and 24b, and the nitrogen gas pressure was adjusted to 13.2 MPa. In addition, the temperature of each of the heaters 18a to 18d was controlled so that the internal temperature of the container 42 was 870°C. The temperature was increased and pressurized over two hours until the internal temperature reached 870°C and the nitrogen gas pressure reached 13.2 MPa. Thereafter, the four actuators 78 were controlled by a sequencer to alternately rotate the pressure vessel 12 clockwise and counterclockwise at 60-second intervals while tilting it at an angle of 10° from the horizontal direction, thereby stirring the melt in the growth vessel 50 for 100 hours to grow a crystal. At this time, the rotation speed of the pressure vessel 12 was set to 5 rpm. Then, the pressure vessel 12 was gradually cooled to room temperature over 30 hours.Thereafter, the growth vessel 50 was removed from the pressure vessel 12, the flux was removed using ethanol, and the Zn-doped GaN crystal plate grown on the seed crystal substrate 54 was collected. In this manner, a Zn-doped high-resistance group 13 nitride (GaN) single crystal was produced as a base substrate for film formation.
[0054] (2) Evaluation of high-resistivity group 13 nitride single crystals The obtained high-resistivity group 13 nitride (GaN) single crystal was a substrate with a diameter of 50.8 mm (2 inches) and a thickness of 1000 μm. When this single crystal was polished and its resistivity was measured at 25°C by Hall measurement, it exceeded the upper limit of measurement. The upper limit of measurement at this time was 1.00×10 4 Next, ohmic electrodes were formed on the front and back of the high-resistance 13-group nitride (GaN) single crystal, and the resistivity was measured at 25°C using the two-terminal method, which was 1.00×10 4 Ω·cm. SIMS analysis also revealed that the Zn concentration in the GaN single crystal was 4.00×10 18 atoms / cm 3 The results are shown in Table 1.
[0055] (3) Formation of ε-Ga2O3 film by mist CVD method Using the mist CVD method, an ε-Ga2O3-based semiconductor layer was formed on the high-resistance group 13 nitride (GaN) single crystal prepared in (1) above, in the following procedure.
[0056] (3a) Mist CVD equipment 6 shows a schematic diagram of the mist CVD apparatus 111 used in this example. The mist CVD apparatus 111 includes a dilution gas source 112a, a carrier gas source 112b, flow rate control valves 113a and 113b, a mist generating source 114, a container 115, an ultrasonic transducer 116, a quartz tube 117, a heater 118, a susceptor 120, and an exhaust port 121. A substrate 119 is placed on the susceptor 120. The flow rate control valve 113a is configured to be able to adjust the flow rate of the dilution gas sent from the dilution gas source 112a, while the flow rate control valve 113b is configured to be able to adjust the flow rate of the carrier gas sent from the carrier gas source 112b. The mist generating source 114 contains a raw material solution 114a, while the container 115 contains water 115a. The ultrasonic transducer 116 is attached to the bottom surface of the container 115. The quartz tube 117 forms a film formation chamber, and a heater 118 is installed on the periphery of the quartz tube 117. The susceptor 120 is made of quartz, and the surface on which the substrate 119 is placed is inclined from the horizontal plane.
[0057] (3b) Preparation of raw solution An aqueous solution of gallium acetylacetonate with a concentration of 0.05 mol / L was prepared, containing 1.5% by volume of 36% hydrochloric acid, and used as the raw material solution 114a.
[0058] (3c) Preparation for film formation The obtained raw material solution 114a was contained in the mist generating source 114. The high resistance group 13 nitride single crystal prepared in the above (1) was placed on the susceptor 120 so that the Ga face was the deposition surface as the substrate 119, and the heater 118 was operated to raise the temperature in the quartz tube 117 to 650°C. Next, the flow rate control valves 113a and 113b were opened to supply the dilution gas and carrier gas from the dilution gas source 112a and carrier gas source 112b into the quartz tube 117, respectively. After the atmosphere in the quartz tube 117 was sufficiently replaced with the dilution gas and carrier gas, the flow rate of the dilution gas was adjusted to 0.5 L / min and the flow rate of the carrier gas was adjusted to 1 L / min, respectively. Nitrogen gas was used as the dilution gas and carrier gas.
[0059] (3d) Film formation The ultrasonic vibrator 116 was vibrated at 2.4 MHz, and the vibration was propagated through the water 115a to the raw material solution 114a, thereby atomizing the raw material solution 114a to generate mist 114b. This mist 114b was introduced into the quartz tube 117, which is a film formation chamber, by a dilution gas and a carrier gas, reacted in the quartz tube 117, and a film was formed on the substrate 119 by CVD reaction on the surface of the substrate 119. Thus, a crystalline semiconductor film (semiconductor layer) was obtained. The film formation time was 9 minutes. Ten samples in which a crystalline semiconductor film was formed on a high-resistance group 13 nitride single crystal were prepared by the above-described steps.
[0060] (4) Evaluation of the semiconductor film (4a) Surface EDS As a result of performing EDS measurement on the film surface on the film formation side (i.e., the side opposite to the high-resistance group 13 nitride single crystal) of the obtained film, only Ga and O were detected, and it was found that the obtained film was a Ga oxide.
[0061] (4b) Surface EBSD Inverse pole figure orientation mapping of the Ga oxide film surface was performed in a field of view of about 50 μm × 10 μm using a SEM (SU-5000, manufactured by Hitachi High-Technologies Corporation) equipped with an electron backscatter diffraction apparatus (EBSD) (Nordlys Nano, manufactured by Oxford Instruments). Using the software (Twist) attached to the apparatus, the crystal information of the space group, unit cell parameters (sides and angles), and atomic positions of ε-Ga2O3 (hexagonal crystal) described in Non-Patent Document 4 (F. Mezzadri, et al., "Crystal Structure and Ferroelectric Properties of ε-Ga2O3Films Grown on (0001)-Sapphire," Inorg. Chem. 2016, 55, 12079-12084) was registered in the database, and EBSD measurement was performed using this.
[0062] The conditions for this EBSD measurement were as follows. <EBSD measurement conditions> · Acceleration voltage: 15 kV · Spot intensity: 70 Working distance: 22.5mm Step size: 0.5μm Specimen tilt angle: 70° Measurement program: Aztec (version 3.3)
[0063] From the obtained inverse pole figure orientation mapping, it was found that the Ga oxide film has a biaxially oriented crystal structure with the c-axis oriented in the normal direction to the substrate and also oriented in-plane. These results confirmed that the obtained semiconductor film is an oriented film with a crystal structure composed of ε-Ga2O3.
[0064] (4c)Zn concentration The Zn concentration in the ε-Ga2O3 film was measured using a D-SIMS (CAMECA IMS-7f). The primary ion species used in the measurement was Cs + The measurement was performed using ions at a primary ion acceleration voltage of 14.5 kV. As a result, the Zn concentration in the ε-Ga2O3 film was 1.00×10 16 atoms / cm 3 The following were confirmed. The results are shown in Table 1.
[0065] (4d) Check for peeling areas Using an optical microscope, ten samples obtained in (3d) above were examined to detect the locations where the ε-Ga2O3 film had peeled off from the base substrate (GaN single crystal). Only one peeled location was found. The results are shown in Table 1.
[0066] Example 2 A laminate was prepared in the same manner as in Example 1, except that in the above (1) the thickness of the high-resistance group 13 nitride single crystal was adjusted to 350 μm by polishing, and in the above (3d) the film formation time was changed to 300 minutes, and various evaluations were carried out. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0067] Example 3 A laminate was prepared in the same manner as in Example 1, except that the film formation time in the above (3d) was 1 minute, and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0068] Example 4 A laminate was prepared in the same manner as in Example 1, except that the film formation time per one time was set to 1 hour and the film formation was repeated 50 times in the above (3d), and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0069] Example 5 A laminate was prepared in the same manner as in Example 1, except that the amount of zinc in (1) was 70 mg, and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0070] Example 6 A laminate was produced in the same manner as in Example 1, except that 1200 mg of zinc was used in (1) above, and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0071] Example 7 A laminate was prepared in the same manner as in Example 3, except that in (1) above, the high-resistance GaN single crystal substrate was replaced with a commercially available AlN single crystal substrate (thickness 450 μm), and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0072] Example 8 (comparison) A laminate was produced in the same manner as in Example 3, except that no zinc was used in (1) above, and various evaluations were carried out. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0073] Example 9 (comparison) In the above (1), except that the thickness of the high-resistance GaN single crystal was thinned to 180 μm, a laminate was produced in the same manner as in Example 3, and various evaluations were carried out. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0074] Example 10 (comparison) A laminate was prepared in the same manner as in Example 5, except that 20 mg of zinc was used in the above (1) and the film formation time was 1 minute in the above (3d), and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0075] Example 11 A laminate was prepared in the same manner as in Example 1, except that 750 mg of iron (Fe) was used instead of zinc in (1) above, and the Fe concentration was measured in (2) and (4c) above, and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0076] Example 12 A laminate was prepared in the same manner as in Example 1, except that 750 mg of manganese (Mn) was used instead of zinc in (1) above, and the Mn concentration was measured in (2) and (4c) above, and various evaluations were performed. The obtained film was confirmed to be ε-Ga2O3. The results are shown in Table 1.
[0077] [Table 1]
Claims
1. ε-Ga 2 O 3 , or ε-Ga 2 O 3 a semiconductor layer composed of a silicon-based solid solution; Resistivity at 25°C is 1.00 x 10 2 A high-resistivity group 13 nitride single crystal having a resistivity of Ω cm or more and a thickness of 200 μm or more; A laminate having a two-layer structure composed of:
2. 2. The laminate according to claim 1, wherein the high-resistance group 13 nitride single crystal is any one single crystal selected from the group consisting of GaN, AlN, and BN.
3. The high-resistance group 13 nitride single crystal is a single crystal of GaN, and contains Zn as a dopant at a concentration of 1.00×10 18 ~2.00 x 10 19 atoms / cm 3 The laminate of claim 2 comprising:
4. The high-resistance group 13 nitride single crystal is a single crystal of GaN, and contains Fe as a dopant at a concentration of 1.00×10 18 ~2.00 x 10 19 atoms / cm 3 The laminate of claim 2 comprising:
5. The high-resistance group 13 nitride single crystal is a single crystal of GaN, and Mn is contained as a dopant in an amount of 1.00×10 18 ~2.00 x 10 19 atoms / cm 3 The laminate of claim 2 comprising:
6. The Zn concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of claims 1 to 5, wherein:
7. The Fe concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of claims 1 to 5, wherein:
8. The Mn concentration in the semiconductor layer is 1.00×10 16 atoms / cm 3 The laminate according to any one of claims 1 to 5, wherein:
9. The thickness t of the semiconductor layer 1 The thickness t of the high-resistance group 13 nitride single crystal 2 Ratio to t 1 / t 2 But, 1.00 x 10 -5 The laminate according to any one of claims 1 to 5, wherein the molecular weight is 1.00 or less.
Citation Information
Patent Citations
Thermal transfer type recording apparatus
JP1985018360A
Motor-operated remote-controlled mirror device
JP1989036538A
Gallium nitride semiconductor substrate, gallium nitride semiconductor device, imaging device, and manufacturing method thereof
JP2019012826A
Method for manufacturing semiconductor device, and semiconductor device
JP2019046984A